A receiver-side power control method for series-series magnetic topology in inductive contactless electric vehicles battery charger application - Bhukya Bhavsingh; Gotluru Suresh Babu; Bhukya Mangu; Ravikumar Bhukya (Institute of Advanced Engineering and Science, 2023)
Wireless power transfer (WPT) can be used to charge the battery conveniently and efficiently. In this paper, the investigation of high-efficiency S/S resonant magnetic topology in inductive wireless battery charging of electric vehicles (EVs) is analyzed, designed, and controlled. To regulate the output power efficiently rather than controlling the supply voltage, novel bidirectional switches are introduced to control the output power by using the duty cycle control method. The output power of the secondary side is derived and discussed based on the fundamental harmonic approximation (FHA) approach. A 1.5 kW, 120 mm distance, and 85 kHz resonance frequency are verified in MATLAB/Simulink.